2021
DOI: 10.2174/1871526520666201016150501
|View full text |Cite
|
Sign up to set email alerts
|

BCG Vaccine, A Ray of Hope in Treating Severe Acute Respiratory Syndrome (SARS)

Abstract: : In December 2019 in Wuhan, China, the Severe Acute Respiratory Syndrome - Corona Virus - 2 (SARS-CoV-2) (also 2019 nCoV) was first discovered. Later WHO declared that SARS-CoV-2 was responsible for Coronavirus Disease 2019 (COVID-19). The round, elliptical or pleomorphic shape of the 2019-nCoV is 60–140 nm in diameter. It comprises a single stranded genome of RNA that comprises 29891 nucleotides, a lipid shell and spike protein, envelops membrane, and hemagglutinin-esterase (HE) proteins. Several therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Numerous experimental studies have shown RAAS inhibition with ARBs and ACEIs to result in a compensatory rise in ACE2 at tissue levels, indicating that these medications may be harmful to SARS-CoV-2. It is also important to note that no conclusive evidence or research has proved that ARBs and ACEIs raise ACE2 levels in body tissue (Paramasivam et al 2020 ; Banerjee et al 2021 ). Several learned organizations, such as the European Society of Cardiology, the International Society of Hypertension, and the European Society of Hypertension already have officially endorsed this, implying that there is no need to resist ARBs or ACEIs in patients who are at risk of COVID-19 infection.…”
Section: Covid-19 and Cardiovascular Diseasesmentioning
confidence: 99%
“…Numerous experimental studies have shown RAAS inhibition with ARBs and ACEIs to result in a compensatory rise in ACE2 at tissue levels, indicating that these medications may be harmful to SARS-CoV-2. It is also important to note that no conclusive evidence or research has proved that ARBs and ACEIs raise ACE2 levels in body tissue (Paramasivam et al 2020 ; Banerjee et al 2021 ). Several learned organizations, such as the European Society of Cardiology, the International Society of Hypertension, and the European Society of Hypertension already have officially endorsed this, implying that there is no need to resist ARBs or ACEIs in patients who are at risk of COVID-19 infection.…”
Section: Covid-19 and Cardiovascular Diseasesmentioning
confidence: 99%
“…Furthermore, COVID-19 patients with severe disease also undergo high levels of D-dimer and an extreme decrease in the platelet count, which may make certain patients vulnerable to acute cerbrovascular events ( Wu et al, 2020 , Wu et al, 2020 ; Naeimi and Ghasemi–Kasman, 2020 ). Thus, patients at risk of contracting a brain vascular disorder are likely to be notified of acute brain cerebrovascular events during CoV infections ( Banerjee et al, 2020 ; Driggin et al, 2020 ).…”
Section: Nervous System Diseases Related To Covid-19 Infectionsmentioning
confidence: 99%
“…Novel coronavirus disease (COVID-19) was diagnosed with flu influenza-like symptoms and respiratory distress in December 2019 in Wuhan, China ( Ali and Alharbi, 2020 ). The virus belongs to the Coronaviridaefamily's -coronavirus subgroup and has an enveloped single-stranded Ribonucleic acid (RNA) genome ( Banerjee et al, 2020 ; Chen et al, 2020 ). SARS-CoV-2 is genetically close to SARS-CoV and MERS-CoV but distinct enough to be considered a novel virus, according to a genetic study ( Andersen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Viral replication usually collapses about 5–7 days subsequent to the episode of symptoms [11] . After 7-10 days of appearance of symptoms, patients move into second phase and become seriously ill due to strong immune reaction and therefore the urgency to shift patient in ICU becomes high because of ARDS or multi-organ failure [12] , [13] , [14] . It has been revealed in 25 COVID-19 studies (involving 4881 severe and non-severe cases) [15] that the patients severely affected with COVID-19 were mostly suffering from diabetes and hypertension [15] .…”
Section: Introductionmentioning
confidence: 99%